Bridging Gaps in Government Policies for Inclusive Education in Indonesia: Menjembatani Kesenjangan dalam Kebijakan Pemerintah untuk Pendidikan Inklusif di Indonesia - Nyoman Suwarta; Ahmad Nurefendi Fradana; Dwi Astutiek; Agus Salim; Joko Susilo; Bambang Koesbandriyo (Academia Open, 2025)
Background: Inclusive education ensures equitable access for students with special needs, yet implementation in Indonesia faces challenges like limited resources, insufficient teacher training, and societal stigma. Knowledge Gap: While studies examine teacher attitudes and institutional challenges, the role of government policy remains underexplored. Aim: To analyze the implementation of government policies on inclusive education. Results: Qualitative analysis revealed gaps in training and funding, contrasting with successful policy instruments supporting inclusion. Novelty: This study identifies disparities between policy frameworks and their practical application. Implications: Collaborative efforts among stakeholders and enhanced cultural support are crucial for effective policy implementation and better educational outcomes. Highlights: Policy Implementation: Gaps exist between inclusive education policies and their practical application, particularly in teacher training and funding. Community Perspectives: Societal stigma toward students with special needs remains a critical barrier to inclusivity. Collaboration Required: A multi-stakeholder approach is essential to align policy objectives with ground-level execution and cultural integration. Keywords: Inclusive Education, Government Policy, Teacher Training, Societal Stigma, Resource Allocation